Microextraction by packed sorbent and HPLC–PDA quantification of multiple anti-inflammatory drugs and fluoroquinolones in human plasma and urine. (3rd November 2016) - D'Angelo, Veronica; Tessari, Francesco; Bellagamba, Giuseppe; De Luca, Elisa; Cifelli, Roberta; Celia, Christian; Primavera, Rosita; Di Francesco, Martina; Paolino, Donatella; Di Marzio, Luisa; Locatelli, Marcello
Abstract: We developed and validated an analytical method based on microextraction packed sorbent (MEPS) and high-performance liquid chromatography (HPLC) coupled to photodiode array (PDA) detector to simultaneously quantify multiple nonsteroidal anti-inflammatory drugs (NSAIDs) and fluoroquinolones (FLQs), which may provide as combination several adverse reactions in nephrology and neurology. The linearity range from LOQs (0.1 μg/mL) to 10 μg/mL, and LODs values were 0.03 μg/mL for both NSAIDs and FLQs. The validation was performed according to international guidelines and the accuracy was tested measuring the precision, intermediate precision and trueness. The drugs stability was tested under different storage conditions (+4 °C and −20 °C) and after three different cycles of freezing and thawing. The method can be a suitable tool to simultaneously detect a possible association of drugs in human biological samples and provide several potentialities for clinical applications, bioequivalence studies, pharmacodynamics and toxicodynamics of different pharmaceutical dosage forms showing NSAIDs and FLQs.